Fulminant Hepatic Failure in Pregnancy and its Association with Viral Hepatitis E (Medical Forum Monthly, 2021)
Objective: To determine the frequency of fulminant hepatic failure in pregnancy and its association with viral hepatitis E.Study Design: A retrospective studyPlace and Duration of Study: This study was conducted at the Department of Obstetrics & Gynecology, Liaquat Medical University Hospital, Hyderabad, from April 2019 to April 2021 for a period of two years.Materials and Methods: One hundred fulminant hepatic failure pregnant ladies were enrolled. Main variables of study were gestational age, duration of disease, IgM (positive/negative) for hepatitis E virus, maternal complications and mortality. Statistical package for social sciences version 23 was used for data analysis. Mean and standard deviation for numerical data like age and gestational age and frequency and percentages for categorical data like IgM (positive/negative).Results: The mean age, gestational age of patients and duration of disease were 26.25±4.87 years, 31.16±3.82 weeks and 2.45±1.14 weeks respectively. Most of the patients had 3 or more weeks of disease. Number of patients n=61 (61.0%) were found to be IgM positive for the hepatitis E virus. Maternal mortality was noted as n=71 (71.0%) and live births were 41 (41.0%). No association was found between age, gestational age and duration of disease (P-value, 0.364, 0.107 and 0.956 respectively).Conclusion: Hepatitis E infection during third trimester of pregnancy can leads to fulminant hepatic failure and associated with number of fetal and maternal complications. Special prevention plan is necessary along with awareness and public health facilities. Timely diagnosis especially IgM anti HEV is mandatory.